2015 17th International Conference on Transparent Optical Networks (ICTON) 2015
DOI: 10.1109/icton.2015.7193567
|View full text |Cite
|
Sign up to set email alerts
|

High performance AWGR PONs in data centre networks

Abstract: The unprecedented advances in Passive Optical Networks (PONs) and their proven performance in access networks have encouraged researcher to investigate the use of passive optics to address the limitations of conventional data centre architectures. In this paper, we present a scalable, high capacity and energy efficient arrayed wave guide grating router (AWGR) PON based data centre architecture to facilitate inter and intra racks communication within data centres. The proposed architecture can be scaled up effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…The PON cell fabric interconnection is designed to be flexible to accommodate any number of PON groups through mathematical model that solves for topology physical interconnection and the wavelength routing and assignment within the cell [9]. The third part of the network is the optical switch (OLT An OLT chassis therefore can accommodate a total of 256 AM ports and hence connect a maximum of 256 PON group.…”
Section: The Architecture Of the Awgr Based Pon Data Center Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…The PON cell fabric interconnection is designed to be flexible to accommodate any number of PON groups through mathematical model that solves for topology physical interconnection and the wavelength routing and assignment within the cell [9]. The third part of the network is the optical switch (OLT An OLT chassis therefore can accommodate a total of 256 AM ports and hence connect a maximum of 256 PON group.…”
Section: The Architecture Of the Awgr Based Pon Data Center Networkmentioning
confidence: 99%
“…We have proposed, compared, and patented five novel designs relaying mostly on PONs to handle intra and inter rack communications [2]. In [9], we have shown that the AWGR-based PON architecture can be scaled up efficiently to hundreds of thousands of servers and have shown energy savings of 45% and 80% compared to the Fat-Tree [10] and BCube [11] architectures respectively. In [12] a Software Defined Network (SDN) based AWGR based PON data center architecture was introduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AWGs are also found in many data center designs to mainly address major concerns raised about the power consumption of IT devices and its impact on global warming in the first place and on the electricity bill in the second place [3]. Such data center architecture designs are promoted and proposed in [4]…”
Section: Introductionmentioning
confidence: 99%